Teori Peluang - Hasibuan, Nuri Syamsika; Septiani, Septiani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to examine the theory of probability, which is a branch of mathematics that studies the likelihood or probability of an event occurring in random phenomena. The main objects in this theory include random variables, stochastic processes, and events that cannot be predicted with certainty but can be analyzed mathematically. The probability value of an event ranges from 0 to 1, where 0 indicates an impossible event and 1 indicates a certain event. Probability theory uses the concept of a sample space as the set of all possible outcomes of an experiment, and an event as a subset of that sample space. Principles such as complementary probability, conditional probability, mutually independent events, as well as the law of large numbers and the central limit theorem form the foundation of probability analysis. This theory is an important foundation for statistics, especially in data processing and decision-making under uncertainty. Besides mathematics and statistics, probability theory is also widely applied in various fields such as physics, finance, and social sciences.